2008
DOI: 10.1007/s10753-008-9093-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inflammatory and Hemostatic Parameters in Female Patients Undergoing Total Knee Arthroplasty Surgery

Abstract: Tendency to hypercoagulation is a common phenomenon in primary osteoarthritis patients (POA) undergoing total knee arthroplasty (TKA) surgery, but the clinical implications of this condition are not clear. Therefore we aimed to evaluate the inflammatory and coagulation parameters in the patient group and find a possible explanation for the tendency to hypercoagulation occurring in plasma and synovia of inflamed joints. Of the evaluated factors involved in inflammation and coagulation, galectin-3, C reactive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
(84 reference statements)
2
24
1
Order By: Relevance
“…The increase might be due to upregulation of Gal-3, especially at inflammatory sites, as a result of disruption of arteries and macrophage production and secretion. Consistent with this finding, certain studies in the literature 5,11,17,20 have reported the presence of an increased level of Gal-3 in physiological and pathological processes, including immune and inflammatory responses, wound repair, and atherosclerosis. However, knowledge about the contribution of Gal-3 in patients with AMI is still scarce; further studies are necessary to elucidate this mechanism.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The increase might be due to upregulation of Gal-3, especially at inflammatory sites, as a result of disruption of arteries and macrophage production and secretion. Consistent with this finding, certain studies in the literature 5,11,17,20 have reported the presence of an increased level of Gal-3 in physiological and pathological processes, including immune and inflammatory responses, wound repair, and atherosclerosis. However, knowledge about the contribution of Gal-3 in patients with AMI is still scarce; further studies are necessary to elucidate this mechanism.…”
supporting
confidence: 79%
“…They found intense immunostaining for Gal-3 in foam cells that were present in the atheromatous plaques in the artery walls. Galectins produced by circulating blood cells or endothelial cells have been reported [18][19][20][21] to induce leukocyte attachment to the endothelium by cross-linking carbohydrates on the respective cell surfaces. The expression of Gal-3 is highly upregulated when monocytes differentiate into macrophages, a step in atherogenesis that follows monocyte recruitment from the peripheral blood to the artery wall and also occurs when in vivo or in vitro macrophages or aortic smooth muscle cells are loaded with lipids and transformed into foam cells.…”
mentioning
confidence: 99%
“…In contrast, arthritis research in humans has for several years emphasized the importance of haemostasis in joint pathologies [1013]. Haemostatic proteins such as TAT and fibrinogen have been detected in human SF, where they have been reported to induce or modulate inflammatory responses [14, 17]. Due to the low number of horses, no such assessment of interaction or of causal relationships between inflammatory and haemostatic biomarkers was made in this study.…”
Section: Discussionmentioning
confidence: 99%
“…24 h at 2–8 °C, then in aliquots at −80 °CWithin 7 monthsNot previously reported in equine synovial fluid, but in synovial fluid of human patients by a colorimetric method using an automatic analyser (Aeroset, USA) [70]FibrinogenBloodCitrate2–8 °CMax. 24 hClauss method, automated coagulometric analyser (ACL 9000, Instrumentation Laboratory, Barcelona, Spain).[22]Synovial fluidCitrate1500 g for 15 min at 20 °CInitially 15–30 min at room temperature then in aliquots at −80 °CWithin 17 monthsQuickVet® Equine Fibrinogen™ Test (Scandinavian Micro Biodevices, Farum, Denmark)Measured in synovial fluid in human osteoarthritis with automatic coagulometer (BFT II Dade Behring, Marburg, Germany) [17]Thrombin-antithrombinBloodCitrate1500 g for 15 min at 20 °CInitially 15–30 min at room temperature then in aliquotsat −80 °CWithin 20 monthsELISA measured in duplicates (Enzygnost TAT micro test kit, Siemens Healthcare Diagnostics, Denmark)[45, 81]Synovial fluidCitrateWithin 20 monthsNot previously reported in equine synovial fluid, but with same assay in synovial fluid of human rheumatoid arthritis and osteoarthritis [14]D-dimerBloodCitrate1500 g for 15 min at 20 °CInitially 15–30 min at room temperature then in aliquots at −80 °CWithin 21 monthsImmunoturbidimetry in duplicates (STA-Liatest D-DI, Diagnostica Stago, Triolab, Denmark)[82, 83]Synovial fluidCitrateWithin 18 months[25, 26], both used a quantitative immune-turbidimetric latex agglutination assay (Miniquant, Biopool, Trinity Biotech, Wicklow, Ireland) EDTA Ethylenediaminetetraacetic acid ELISA Enzyme-linked immunosorbent assay …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation